Retail's seismic shift : how to shift faster, respond better, and win customer loyalty - Dart, Michael, ....-; Lewis, Robin, ....- (New York : St. Martin's Press, 2017)
Compared to 25 years ago, todays retail experience is a world apart. Almost anything can be ordered, delivered and picked up rapidly, often customized to personal preferences at no extra cost. The smartphone has created a world of limitless consumer expectation and logistical possibility. So how much further can it go? What will the retail experience look like in ten, twenty, or even fifty yearsand how should companies, big and small, be preparing? Amazon may still loom large, say industry experts Robin Lewis and Michael Dart, but now theyll actually be profitable, as mobile shopping becomes the norm. More importantly, the primacy of access over ownership, and experience over material goods, will force retailers to transform their offerings. Demographic trends, like the glut of seniors and the declining marriage rate, and societal trends, like income polarization and continued urbanization, will have surprising effects on which brands and products take center stage. And the double-edged sword of technology will be fully apparent: no more cards or cash, but pervasive fear of fraud and surveillance from the dark Web and the rise of A.I.. In their previous book, The New Rules of Retail, Lewis and Dart predicted nearly every defining characteristic of todays marketplaceand the industry snapped it up in two editions. Now, in Retail's Seismic Shift, they do the same for the next era, where retailers will have to be ready for anything.